A Validated High-Performance Thin-Layer Chromatography Method for Analyzing Fat-Soluble Vitamins in Commercial Pharmaceutical Preparations - K. M. Yasif Kayes Sikdar; Md Khairul Islam; Tomislav Sostaric; Lee Yong Lim; Cornelia Locher (Applied Sciences)
A simple, cost-effective, and efficient novel high-performance thin-layer chromatography (HPTLC) tool was developed and validated in accordance with International Conference on Harmonisation (ICH) guidelines for the detection and quantification of four fat-soluble vitamins, D2, D3, E, and K1, using chloroform: cyclohexane (55:45, v/v) as mobile phase. The detection and quantification limits were found to be 30.86 and 93.52 ng/band for vitamin D2, 19.44 and 58.92 ng/band for vitamin D3, 14.17 and 42.95 ng/band for vitamin E, and 0.86 and 2.61 ng/band for vitamin K1, which were similar or lower than those reported in previous methods. The advantage of the developed method is that it uses a simple mobile phase in a single development step and has low detection and quantification limits. The application of the developed HPTLC method was successfully demonstrated with the quantitative analysis of these vitamins in some commercially available pharmaceutical preparations.